Yamato Achondrite Polymict Breccias - Miyamoto, Masamichi; Takeda, Hiroshi; Yanai, Keizo (1978)
P(論文) Electron microprobe studies have been made of pyroxenes from Yamato-7307 and Yamato-74159. Both meteorites show the brecciated texture. Yamato-7307 was identified as howardite by us previously. It contains pyroxenes similar to those of diogenites and eucrites. However, Yamato-74159 contains various pyroxenes, calcic plagioclase, and other minerals and lithic clasts of only eucritic affinity. Within the thin section we have examined, there was found no diogenitic pyroxene. Therefore, Yamato-74159 may best be described as a eucrite polymict breccia. These two meteorites can be explained by the surface brecciation process of a proposed layered crust model on an achondrite parent body. departmental bulletin paper